A Novel Method of Extraction and Purification of Bacterial DNA for PCR Detection of MecA, 16SrRNA, VanB - Abdullah, Raheem Hashim; Hassoni, Adil Abaed (Journal of Medical Genetics and Clinical Biology, 2024)
Bacteria are the main pest of nosocomial infections in healthcare facilities around the world. The aim of this study is to modify and minimize the amount of time, while still having no influence on the extraction's purity of DNA the method of extracting the DNA molecule and compare it with other methods that take longer to extract and purify DNA. This study examined two processes for isolating DNA from Gram-positive bacterial species: a boiling method and an enzymatic method that took one hour. In addition, the collected DNA was subjected to spectrophotometry, agarose gel electrophoresis, and PCR for both quantitative and qualitative examination. The results presented in this work show that boiling method pretreatment facilitates efficient cell lysis and DNA extraction, leading to increased yields of isolated bacterial DNA. In addition, DNA suitability for PCR-based identification of mecA,16SrRNA, VanB to Gram positive S. aureus strains was analyzed. Our findings demonstrated that the DNA generated by this simple approach is low-cost, quick, and safe, and that the process may be utilized in PCR methods on a wide range of gram-positive and gram negative species, as well as in laboratories without the necessary materials, tools, or technology